NILAI-NILAI RELIGIUS DALAM KISAH NYATA “ADA YANG ABADI” KARYA EIDELWEIS ALMIRA DAN IMPLIKASI PADA PEMBELAJARAN BAHASA INDONESIA - Zebua, Seprianus (Universitas Nias Raya, 2025)
The background of this research is that there are still students with unstable conditions, so it is hoped that strong religious values ​​will be instilled so that they will be embedded and have an influence on students' daily lives. This type of research is descriptive qualitative research. The data source is writing or sentences in the true story There is an Immortal by Eidelweis Almira which contains religious values. The research results show that the true story